ANALISIS PENDAPATAN USAHA TANI NENAS DI DESA LOBONG KECAMATAN PASSI BARAT KABUPATEN BOLAANG MONGONDOW - Seplianto Maarende; Caroline B.D. Pakasi; Juliana Mandei (COCOS, 2013)
ABSRACTSEPLIANTO MAARENDE, Analysis Income of Pineapple Farm In LobongPakasi as chairman and Celsius Talumingan and Juliana Mandei as member.This study aims to determine how much income and expense requiredpineapple farming. This research is expected to benefit the pineapple farmers toincrease earned income and be able to manage with a pineapple farm better andcan provide benefits in the form of information for farmers and those who need it.This study was conducted in Bolaang Mongondow with data retrievaldirectly from farmers in the village of pineapples Lobong Bolaang Mongondow.The data is then analyzed using analysis revenue analysis followed by analysis ofReturn Cost Ratio (Return R / C), known as the ratio between the total cost ofproduction revenue.Pineapple farm income calculation is done in stages five times the harvest.With a total cost of Rp Rp. 18.922.000 with total revenue of Rp. 30.387.000.Pinapple farmer earn incomes of Rp. 11. 465.500 for every harvest period, each inevery hectare. Results of these calculations can be conclude that the pineapplefarm in the village of Lobong Bolaang Mongondow feasible to run because it isgenerally very favorable for obtaining the value of R / C of 1.60. It means every 1rupiah cost given by farmer can produce 1,60 income. These shows that pinapplefarming in Lobong Village have economic advantages.Village of Bolaang Mongondow Regency under the guidance of Caroline B.D.